Factors Influencing Young Audience Preferences for Digital Platforms in Indonesia - Mochammad Abdul Machfud; Arieviena Ayu Laksmi; Tangkin Hong (Vokasi UNESA Bulletin of Engineering, Technology and Applied Science, 2024)
The rapid development of digital technology and the widespread adoption of the internet have significantly transformed media consumption patterns, especially among young audiences in Indonesia. This study uniquely explores the preferences and motivations of Indonesian youth (ages 15-30) in selecting digital platforms over traditional media, applying the Theory of Planned Behavior (TPB) as a framework. TPB posits that Attitude Toward Behavior(ATB), Subjective Norms(SN), and Perceived Behavioral Control (PBC) are keyfactors influencing behavioral intentions. The results reveal distinct differences from prior research: SN and PBCemerged as dominant influencers, whereas ATBhad minimal impact. These findings underline the critical roles of social validation and platform usability in shaping preferences. Implications of this study include guiding media providers to develop strategies that cater to the social and functional needs of young Indonesians, ensuring sustained engagement with digital platforms.